The Boiling Circle, the Rotating Circle - Babaei, Ali (Տիգրան Մեծ)
In theological sources, many symbols are used to explain the transcendent truths of existence. Among the shapes, the circle has the most use of a symbol which is important for religions, philosophers, and mys-tics. Usually, when talking about a circle, a round line appears that starts from a point on the surface and ends again at that point. In this way of drawing a circle, the most exterior and superficial epistemological symbols are explained. Contrary, the present article proposes a novel way of drawing a circle, and with this approach, examines some philosophical concepts. We call this drawing “Boiling Circle” because the rays are coming out boiling from the centre. We also have analyzed and introduced a unique example of a mystical-philosophical-religious Architectural building, during which a circular spring has been built. Its water comes out boiling of the centre and fills the five circles within itself and twelve eyes around it. This article begins with the drawing of a boiling circle, explains the philosophical symbols of the boiling circle and boiling spring according to Islamic mysticism, and compares and expresses the differences between the symbols of the two circles.
Keywords: Philosophy; Traditions